When abortion was a crime : women, medicine, and law in the United States, 1867-1973 - Reagan, Leslie J. (University of California Press, 1997)
As we approach the 30th anniversary of Roe v. Wade, it's crucial to look back to the time when abortion was illegal. Leslie Reagan traces the practice and policing of abortion, which although illegal was nonetheless widely available, but always with threats for both doctor and patient. In a time when many young women don't even know that there was a period when abortion was a crime, this work offers chilling and vital lessons of importance to everyone. The linking of the words "abortion" and "crime" emphasizes the difficult and painful history that is the focus of Leslie J. Reagan's important b.
Keywords: Umschulungswerkstätten für Siedler und Auswanderer -- Bitterfeld; Abortion -- United States -- History.; Abortion services -- United States -- History.; Abortion -- Law and legislation -- United States -- History.; Abortion, Criminal -- history; Abortion, Induced -- legislation & jurisprudence; Women's Health Services -- history; United States; Avortement -- États-Unis -- Histoire.; Cliniques d'avortement -- États-Unis -- Histoire.; Avortement -- Droit -- États-Unis -- Histoire.; SOCIAL SCIENCE -- Abortion & Birth Control.; MEDICAL -- Health Policy.; Abortion; Abortion -- Law and legislation; Abortion services; Schwangerschaftsabbruch; Strafrecht; USA; Abortus provocatus.; Sociale aspecten.; Juridische aspecten.; Medische aspecten.; 19th century.; abortion rights.; abortion.; american history.; bodily autonomy.; childbirth.; civil liberties.; court cases.; crime.; health care.; human body.; illegal abortion.; law and order.; legal issues.; medical care.; medical issues.; personal freedom.; pregnancy.; privacy.; prosecution.; right to choose.; roe v wade.; sexual freedom.; sexuality.; supreme court cases.; supreme court.; transcripts.; trial.; true story.; united states history.; us history.; womens issues.; womens right to choose.; Legislation; statutes.; law codes.; Statutes and codes; Session laws; History; Statutes and codes.; Session laws.; Lois et codes.